Climate change as the defining crisis for the 21st century - Marques, Viriato Soromenho (2014)
In his first inaugural speech, read on the 4th March 1933, President Franklin Delano Roosevelt depicted the somber landscape of his country ravaged by poverty, unemployment, and despair. However, he saw that amidst the overwhelming bitterness there was a glimpse of hope: “Nature still offers her bounty".